The Influence of Financial Literacy, Income, Financial Behavior, and Risk Perception on Investment Decisions of Generation Z in Medan City - Silvani Riska Ayuni; Noni Ardian; Geby Citra Ananda (Jurnal Fokus Manajemen, 2026)
the purpose of this study is to determine the investment decisions of generation z in Medan City. Investment decisions in generation z, income on investment decisions in generation z, financial behavior on investment decisions in generation z and also risk perception on investment decisions in generation z. in this method using quantitative methods with data collection techniques using purposive sampling tecniques and using the Cochran formula. Tha sample in this study is unknown. Data collection in this study uses goggle form. Technical data analysis uses SPSS 27. The results of this study indicate that 1) financial litetacy has a positive and significant influence on investment decisions; 2) income has a positive and significant influence on investment decisions; 3) financial behavior has a positive and significant influence on investment decisions; 4) risk perception has a positive and significant influence on investment decisions; 5) financial literacy income financial behavior and risk perception have a positive and significant influence on investment decisions.